Fracture mechanics analysis for a mooring system subjected to Gaussian load processes. (1st May 2018) - Xue, Xutian; Chen, Nian-Zhong
Highlights: A fracture mechanics based method for fatigue analysis of an offshore mooring system subjected to Gaussian load processes was presented. The methods for predict the combined loading process induced by the motions of wave frequency (WF) and low frequency (LF) were investigated. The comparison between the narrow-band method, general wide-band methods, and dual narrow-band methods applied to predict the combined mooring line tension was conducted. Abstract: An investigation on the fracture mechanics (FM) analysis using various load combination methods for a mooring system subjected to Gaussian load processes is conducted in this paper. Low frequency (LF) and wave frequency (WF) tensions of mooring lines are predicted by a frequency-domain analysis taking into account environmental effects including wind, wave and current. The LF and WF load processes are regarded as two random processes. The narrow-band method, general wide-band methods (Dirlik method and Tovo and Benasciutti method), and dual narrow-band methods (Jiao and Moan method, Fu and Cebon method and modified Fu and Cebon method) are used for predicting the combined load induced by LF and WF motions in the FM analysis. A comparison between mooring fatigue lives predicted by the FM analysis using these load combination methods is performed and the results show that the FM analysis based on the narrow-band method generally offers the most conservative fatigue life prediction and the difference of fatigue lives of mooring chains estimated based on general wide-band methods and dual narrow-band methods is not significant. However, in some cases, the FM analysis based on Dirlik method, Jiao and Moan method, Fu and Cebon method or modified Fu and Cebon method even provides more conservative results compared with the narrow-band method.